RITUS BELUK DALAM PERSPEKTIF ESTETIKA PARADOKS - Sri Sutrianti (Jurnal Budaya Nusantara, 2022)
Beluk ritual ceremony, is a form of belief in agrarian society, especially field farmers. In the beginning, Beluk was a form of calling between farmers in far-flung huts, to avoid fear of wild animals in forest areas. The way of connecting with each other is in the form of a song with a loud or high tone. A paradoxical aesthetic theory approach with research methods through library and internet media, as well as a psychological perspective is very possible, because at that time the farmers were trying to open the fields for their livelihood. But the ancestral ordinances made a value of how the living system they built at that time. Like what has been done until now in the Ciapus community, Banjaran District, Bandung Regency. A proof that the current form of the Beluk rite proves the representation of his ancestors who built a system of connectedness between nature and human life. This means that life experience which is manifested in a way of life, is a form of belief in determining the system of “live and living”